Potential for Tax Collection Bird Nests Walet, Bantan Sub-District, Bengkalis Regency - Yunita Sari; Novira Sartika (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyse the potential for collecting swiftlet nest tax in Bantan Subdistrict, Bengkalis Regency, with focus on tax revenue, collection potential, obstacles encountered, and government efforts to optimise revenue. Swiftlet nest tax is a strategic source of Local Own-Source Revenue given the prevalence of swiftlet farming in the coastal area of Bengkalis. This study uses a descriptive method with a qualitative approach through in-depth interviews with the Head of the Technical Implementation Unit (UPT) and the District Revenue Administration staff in Bantan Subdistrict, as well as 20 swiftlet entrepreneurs spread across various villages. The results show that swallow nest tax revenue fluctuated during the 2021–2025 period, influenced by a 50% decline in selling prices and production instability. The potential for tax collection has not been optimally explored due to the gap between self-assessment regulations and field practices, low taxpayer understanding of the applicable rates (10%), and the limited capacity of officers to reach all business units. Efforts made by the local government include socialisation, data collection, implementation of the SIPBUKAS application, and multisectoral coordination. This study recommends the application of progressive rates based on production volume, strengthening tax literacy, and integrating a more inclusive digital system.